Site-Specific Fertilizer Recommendation for Barley (Hordeum vulgare L.) Using the QUEFTS Model in Wolaita Zone in Southern Ethiopia - Mesfin Kassa; Wasie Halie; Fassil Kebede (Applied and Environmental Soil Science)
Although Ethiopia is a center of barley domestication and diversity, and barley has an important place in African dry land agriculture due to its resilience to wide-ranging stresses; the average yield continues to be low, mainly due to low soil fertility. Site-specific fertilizer recommendation for barley in Wolaita, Ethiopia, has a pivotal role not only in optimizing barley productivity but also in maintaining ecological balance. Thus, this study was conducted to assess the relationship between grain yield and site-specific nutrient requirements for a target yield using a Quantitative Evaluation of the Fertility of Tropical Soil (QUEFTS) model. The data input was derived from field experiments predominantly in the major barley production areas of Wolaita, Ethiopia. Calibration of the QUEFTS model was estimated by describing the two boundary lines of the maximum accumulation and dilution of N, P, and K contents targeting the barley grain yield. The study revealed that balanced nutrient requirements estimated by the QUEFTS model had a good correlation between the simulated and observed grain yields (r2 = 0.82∗, 0.88∗, and 0.83∗) for different sites, namely, Doga Mashido, Kokate, and Gurimo Koyisha, respectively, while evaluation of the QUEFTS model by U-Theil values showed a good agreement between the simulated and observed yields. Therefore, the study concluded that the QUEFTS model can be used for determining nutrient requirements of crops, thereby contributing to the development of site-specific fertilizer recommendations.